Metabolomics analysis reveals distinct profiles of nonmuscle‐invasive and muscle‐invasive bladder cancer. (1st August 2017) - Sahu, Divya; Lotan, Yair; Wittmann, Bryan; Neri, Bruce; Hansel, Donna E.
Abstract: Urothelial carcinoma is the most common form of bladder cancer, but pathway changes that occur with stage‐wise progression have not been well defined. We used a metabolomics approach to identify potential metabolic pathways uniquely altered in normal urothelium, nonmuscle‐invasive bladder cancer (NMIBC), and muscle‐invasive bladder cancer (MIBC). We performed global metabolomic profiling using GC‐mass spectrometry (MS) and LC‐MS platforms to identify metabolite signatures between normal urothelium and high‐grade urothelial carcinoma of different stages. Pathways globally dysregulated in cancer relative to normal urothelium included glucose, tricarboxylic acid (TCA) cycle, lipid, amino acid, and nucleotide pathways. Urothelial carcinoma showed elevated glucose utilization for glycolysis and increased sorbitol pathway intermediates, consistent with Warburg effect. Anaplerosis to sustain energy production suggested by increased late TCA cycle intermediates, amino acids, and dipeptides occurs in bladder cancer. Urothelial carcinoma also shows altered membrane lipid membrane metabolism and differential derivation of nucleic acid components pyrimidine and purine. In stage comparison, MIBC appears to preferentially enhance cyclooxygenase (COX) and lipoxygenase (LOX) signaling, increase heme catabolism, and alter nicotinamide adenine dinucleotide (NAD+) synthesis with a possible influence from associated inflammatory cells. We identify numerous metabolomic alterations in NMIBC and MIBC that likely reflect underlying pathway changes. Differential pathway activity may have value in designing stage‐specific novel therapeutics in urothelial carcinoma. Abstract : Using a highly sensitive metabolomics approach, we identified multiple pathway changes between normal urothelium and high‐grade urothelial carcinoma and between high‐grade carcinomas of different stages. Several of these differential metabolite profiles suggest the potential for unique targeted therapy in NMIBC and MIBC populations.